Avaliação das condições higiênico-sanitárias em unidades de alimentação e nutrição de escolas municipais do estado do Tocantins - Souza, Ana Carolina de (Universidade Federal do Tocantins, 2023)
The objective of this study was to rate the sanitary hygienic conditions of the Food and Nutrition Units of Tocantins State Public Schools, monitored by the Collaborating Center on Food and Nutrition of the Federal University of Tocantins (CECANE / UFT). The descriptive study used a semi-structured form of quantitative approach with questions about handlers, buildings and facilities, equipment and utensils, storage area, quality control and inventory control. The data collection was performed from March to August 2018 and the data obtained were transformed into percentages. The results showed that all schools analyzed showed non-compliance with the rules governing Good Practices of Food Manufacturing, being guided through an action plan of corrective actions, including the timeframe for execution, who should do it, where it would be executed and the legal basis for such determination. Therefore, the study showed that there is a need for improvements in the feeding units of municipal public schools. Thus, it is necessaryto follow up with a professional nutritionist who elaborates control measures, and monitoring, pointing the need for interventions by management to enable the provision of safe food for students.